The Specialist Palliative Care Nurses’ in an Italian Hospital: role, competences, and activities.: Specialist Palliative Care Nurses’ profile. - Autelitano, Cristina; Bertocchi, Elisabetta; Artioli, Giovanna; Alquati, Sara; Tanzi, Silvia (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Many authors tried to clarify the palliative care nurses’ role, overall in the home care setting, but little is known in different settings of care. We aim to present a Specialist profile of palliative care (PC) nurses in an Italian hospital-based Palliative Care Unit.Methods: With an organizational case study approach, we conducted a literature review on PC nurse’s role, and we presented the Specialist PC nurses’ profile, describing competences and key related activities.Results: Our specialist profile highlights that clinical activities are similar to the experiences described in the literature (symptom assessment and management, communication, interprofessional work), while training and research activities are new fields of interest that it’s important to explore and promote, most of all in our country.Conclusions: Sustaining the flexibility of the role, being recognized by colleagues and keeping the three dimensions connected are the major challenges: drawing up a specialist palliative care nurses’ profile can help the team to better define the role framework in an interdisciplinary context.